A Method to Mitigate the Effects of Strong Geomagnetic Storm on GNSS Precise Point Positioning. Issue 1 (10th January 2022) - Luo, Xiaomin; Du, Junfeng; Lou, Yidong; Gu, Shengfeng; Yue, Xinan; Liu, Jingbin; Chen, Biyan
Abstract: Geomagnetic storm can affect the performance of Global Navigation Satellite System (GNSS) precise positioning services. To mitigate the adverse effects of strong geomagnetic storms, we propose to establish the geometry‐free (GF) cycle slip threshold model based on ionospheric disturbance index rate of total electron content index to reduce the false detection rate of cycle slip in GNSS precise point positioning (PPP) during strong storm periods, thus improving the accuracy and reliability of GNSS PPP. The performance of our proposed model is validated by using 171 International GNSS Service (IGS) tracking stations data on 8 September 2017. The analysis indicates that compared with conventional PPP scheme, the proposed model can improve the positioning accuracy by approximately 14.0% (36.8%) and 23.1% (51.5%) in the horizonal and vertical components for global (high latitudes) stations. Furthermore, the availability of our proposed model is also validated by PPP experiments using 379 IGS tracking stations data during another strong storm occurred on 26 August 2018. Plain Language Summary: Global Navigation Satellite System (GNSS) precise point positioning (PPP) can achieve decimeter or even millimeter levels of positioning accuracy in general. However, this accuracy will be degraded significantly under the strong geomagnetic storm, which is a major disturbance of Earth's magnetosphere that occurs when there is a very efficient exchange of energy from the solar wind into the space environment surrounding Earth. Strong geomagnetic storm associated with ionospheric disturbances can decrease the quality of GNSS measurements or even result in GNSS signals loss of lock known as cycle slip, thus affecting the availability and reliability of the common data processing methods of GNSS PPP. In this study, we investigate the limitations of common threshold in cycle slip detection of GNSS data processing. It is found that the cycle slip detection observation shows close relationship to ionospheric disturbance index ROTI (rate of total electron content index), so we propose to establish the cycle slip threshold model based on ionospheric disturbance index ROTI. GNSS PPP experiments based on abundant International GNSS Service stations data indicate that the proposed model can effectively improve the positioning accuracy especially those stations located at high latitudes. Key Points: Strong geomagnetic storm can significantly degrade the performance of Global Navigation Satellite System (GNSS) precise point positioning (PPP) Geometry‐free cycle slip detection observation shows close relationship to the ionospheric disturbance index rate of total electron content index Positioning accuracy of GNSS PPP based on cycle slip threshold model is generally better than that of conventional PPP